MENS REA - Dr. Neeraj Malik (Innovative Research Thoughts, 2024)
Humans naturally discern purpose from unexpected outcomes. Small toddlers typically learn "I didn't mean to" as an excuse. Thus, pure supposition suggests that the ancient law held men accountable exclusively for their purposeful wrongdoings. All evidence suggests otherwise. "Law in its earliest days tries to make men answer for all the obvious ills their deeds cause"[1] It is sometimes believed that there is one state of mind common to all crimes, however other crimes need a different mental ingredient. The presumption is: “State-of-mind-X is common to all crimes and is sufficient for many, but some offences require some additional mental element, such as state-of-mind-Y or Z.”[2] Care must be taken to be sure that such a formula does not include too much. A person's mental condition may be too immature for mens rea. State-of-mind-X requires a person who is not too young. Again, for state-of-mind-X the mental faculties must not be too greatly disturbed by mental disease, and under certain circumstances they must not have been misled by reasonable mistake of fact, or have been constrained by compulsion.[3] Without going further into detail it is sufficient to point out the need of excluding every mental pattern which contains any factor sufficient in law to exculpate one who has done particular deed in question. If every such factor is excluded and there is present an intent to do the deed which constitutes the actus reus of a certain offense, the result may be said to be state-of-mind-X. It is necessary to add, however, that for certain crimes it will be possible to substitute some other mental factor for the actual intent to do the actus reus. In brief, while state-of-mind-X has certain factors which remain constant, these have to do with the general outlines of the mental pattern rather than with the minute details.